2019
DOI: 10.3390/sym11070841
|View full text |Cite
|
Sign up to set email alerts
|

Global Embeddings of BTZ and Schwarzschild-ADS Type Black Holes in a Flat Space

Abstract: We study the problem of construction of global isometric embedding for spherically symmetric black holes with negative cosmological constant in various dimensions. Firstly, we show that there is no such embedding for 4D RN-AdS black hole in 6D flat ambient space, completing the classification which we started earlier. Then we construct an explicit embedding of non-spinning BTZ black hole in 6D flat ambient space. Using this embedding as an anzats, we then construct a global explicit embedding of (d)-dimensiona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…As in the case of the BTZ black hole, one may construct thermodynamic-like quantities for the accelerating observers that satisfy the laws of thermodynamics. Although reasonable in this context, there is no independent check -as far as I am aware -in the literature on the validity of the expression for the entropy, equation (33). Possible work terms are discussed in appendix C.…”
Section: Schwarzschild Spacetimesmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the case of the BTZ black hole, one may construct thermodynamic-like quantities for the accelerating observers that satisfy the laws of thermodynamics. Although reasonable in this context, there is no independent check -as far as I am aware -in the literature on the validity of the expression for the entropy, equation (33). Possible work terms are discussed in appendix C.…”
Section: Schwarzschild Spacetimesmentioning
confidence: 99%
“…4 Since Newton's constant, the speed of light, and mass do not create a length in (2 + 1)-dimensional gravity, the model must have an additional scale [33].…”
Section: Btz Spacetimesmentioning
confidence: 99%
“…We emphasize that the JCF theorem consider only local embeddings, and when passing to global embeddings, the required dimension of the ambient space increases sharply [3]. However, in specific cases, even for global embeddings, the class of the embedding can be smaller, see, for example, [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The only global embedding [7] turns out to be closely related to the maximum analytic extension of the Schwarzschild metric by the Kruskal-Shekeres coordinates (see the note at the end of [7]). In general, a lot of works have been devoted to the construction of explicit embeddings of various black holes, including charged and rotating ones; see, for example, the links in [5]. Other physically interesting metrics include various cosmological models, e.g., Friedmann-Robertson-Walker metric that describe the expanding universe.…”
Section: Introductionmentioning
confidence: 99%
“…Deser and Levin [6][7][8] showed that the Hawking temperature for a fiducial observer in a curved spacetime can be considered as the Unruh one for a uniformly accelerated observer in a higher-dimensional flat spacetime. Since then, there have been a lot of works on the GEMS approach to confirm these ideas in various other spacetimes [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] and an interesting extension to embedding gravity [25][26][27][28]. Later, Brynjolfsson and Thorlacius (BT) [29] introduced a local temperature measured by a freely falling observer in the GEMS method.…”
Section: Introductionmentioning
confidence: 99%